Service Integration and Management (SIAM"! Professional Body of Knowledge (BoK), Second edition - Agutter, Claire (IT Governance Publishing, 2021)
Service Integration and Management (SIAM™) Professional Body of Knowledge (BoK), Second edition has been updated to reflect changes to the market and is the official guide for the EXIN SIAM™ Professional certification. Prepare for your SIAM™ Professional exam and understand how SIAM can benefit your organization.
Online resource; Title from title page (viewed July 29, 2021)